Application Curriculum of Islamic Education Based on Designing Curriculum Management By Paul A. Nelson - Ahmad Halid; Siti Nursyamsiyah; Ahmad Ta’rifin; Saifaldin Idris Onia (Journal of Islamic Education Research, 2024)
This research is part of the reaction to the admiration of Paul A Nelson's concept in designing the Education curriculum entitled "Curriculum Management By Design" The author wishes to examine and apply the work to the world of development or management of Islamic Education by using the library method applying the concept of data triangulation by analyzing data from strong sources of at least three data sources such as the work of Mastuhu, Ahmad Halid and Law No. 20 of 2003, Tony Bush, Nur Hamim and Tilar, H.A.R. and Nugroho. It was then used as material to analyze or support the results of this study. The results of this study show that the Islamic Education curriculum can be designed by applying three domains of Paul A Nelson's version, namely (1) Perception of reality, that the Islamic Education curriculum designed based on the reality of the needs of society now and in the future. (2) Human Processes, namely the Islamic education curriculum should be able to humanize humans by presenting humanistic education can be left both the sensitivity of individual members. It is necessary to develop a curriculum area that focuses on basic aspects of several animals called humans (3) Human Attitudes and Values, that the Islamic Education Curriculum develops attitudes and values ??that apply in the educational area, developed based on local wisdom and upholding the Attitudes and Values ??that exist in society.